Role of mechanical flow for actin network organization. (May 2019) - Kang, Byungjun; Jo, Seunghan; Baek, Jonghyeok; Nakamura, Fumihiko; Hwang, Wonmuk; Lee, Hyungsuk
Graphical abstract: Abstract: The major cytoskeletal protein actin forms complex networks to provide structural support and perform vital functions in cells. In vitro studies have revealed that the structure of the higher-order actin network is determined primarily by the type of actin binding protein (ABP). By comparison, there are far fewer studies about the role of the mechanical environment for the organization of the actin network. In particular, the duration over which cells reorganize their shape in response to functional demands is relatively short compared to the in vitro protein polymerization time, suggesting that such changes can influence the actin network formation. We hypothesize that mechanical flows in the cytoplasm generated by exogenous and endogenous stimulation play a key role in the spatiotemporal regulation of the actin architecture. To mimic cytoplasmic streaming, we generated a circulating flow using surface acoustic wave in a microfluidic channel and investigated its effect on the formation of networks by actin and ABPs. We found that the mechanical flow affected the orientation and thickness of actin bundles, depending on the type and concentration of ABPs. Our computational model shows that the extent of alignment and thickness of actin bundle are determined by the balance between flow-induced drag forces and the tendency of ABPs to crosslink actin filaments at given angles. These results suggest that local intracellular flows can affect the assembly dynamics and morphology of the actin cytoskeleton. Statement of Significance: Spatiotemporal regulation of actin cytoskeleton structure is essential in many cellular functions. It has been shown that mechanical cues including an applied force and geometric boundary can alter the structural characteristics of actin network. However, even though the cytoplasm accounts for a large portion of the cell volume, the effect of the cytoplasmic streaming flow produced during cell dynamics on actin network organization has not been reported. In this study, we demonstrated that the mechanical flow exerted during actin network organization play an important role in determining the orientation and dimension of actin bundle network. Our result will be beneficial in understanding the mechanism of the actin network reorganization occurred during physiological and pathological processes.